The psychological impact of major disasters on Japan’s medical system: An SNS text analysis - Tomoya Kitayama; Kanae Nishimura (PLoS ONE, 2026)
A major disaster creates an extraordinary situation for medical system. The aim of this study is to evaluate the impact of infrastructure damage caused by a major earthquake on the medical systems in Japan. In this study, we analyzed the content of X (formerly Twitter) to assess the impact of the Noto Peninsula Earthquake that occurred on January 1, 2024 on the medical system, including psychological aspects. Posts including the term “prescription records” were compiled from October 2023 to March 2024. ML-Ask, a python library, was used to evaluate the emotional register of the post basis on ten elements: Joy, Fondness, Relief, Gloom, Dislike, Anger, Fear, Shame, Excitement, and Surprise. The presence of earthquake-related terms was prominent in tweets about prescription records in January, but not in February or March, 2024. The analysis found that in January, words associated with negative emotions were related to the disaster, infrastructure and medical system. From the results of the hierarchical cluster analysis of posts in January, the primary factor triggered negative emotions during the earthquake was the unreliability of electronic medical systems following the loss of power supply. These results suggest that during the earthquake in Japan, a significant number of people harbored negative sentiments toward electronic medical systems and questioned their reliability in disaster situations.